Clinical evaluation of fatigue in Japanese patients with Parkinson's disease. Issue 5 (6th July 2014) - Tanaka, Kenichiro; Wada‐Isoe, Kenji; Yamamoto, Mikie; Tagashira, Shugo; Tajiri, Yuki; Nakashita, Satoko; Nakashima, Kenji
Abstract Background Fatigue is a common nonmotor symptom of Parkinson's disease (PD). Although the causes of fatigue were estimated in the previous reports, fatigue is not fully understood. To determine the frequency of and factors related to fatigue in patients with PD, we carried out clinical assessments in our university hospital. Methods We used the Japanese version of the Parkinson Fatigue Scale (J‐PFS). The J‐PFS was administered to 110 patients with PD, and a cutoff point of 3.3 was used for the diagnosis of fatigue. Subsequently, demographic characteristics, clinical features, and medications utilized were evaluated to elucidate the factors related to fatigue. In particular, we focused on the relationship between fatigue and gait disorder assessed via the portable gait rhythmogram. Results The frequency of fatigue in patients with PD was 52.7%. Univariate analysis revealed that factors significantly associated with fatigue were many motor symptoms and nonmotor symptoms. In addition, multivariate analysis revealed that gait disorder and constipation were independent factors related to fatigue. Furthermore, short‐step walking and bradykinesia in gait disorder had especially a relationship with fatigue. Conclusions More than half of our patients were judged having fatigue. Several factors, including motor and nonmotor symptoms, might be related to fatigue in patients with PD.